2023
DOI: 10.1111/1468-0009.12604
|View full text |Cite
|
Sign up to set email alerts
|

Have States Reduced Obesity by Legislating More Physical Activity in Elementary School?

Abstract: Between 1998 and 2016, 24 states and the District of Columbia passed laws meant to increase the time that children spent in physical education (PE) or other school‐based physical activity (PA). Schools largely disregarded changes to PE/PA laws, which did not increase the time that children spent in PE or recess and did not reduce body mass index, overweight, or obesity. Closer oversight of schools would be needed to improve compliance with state PE and PA laws. Yet, even with better compliance, we estimate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Reducing academic anxiety and stress will lead to better academic performance (51) , but it may also help to promote health behaviours and outcomes (52) . A recent study also emphasises that conventional physical education and other school-based physical activities alone are not sufficient to prevent the obesity epidemic (53) . Yet, further research is needed to expand this study to explore the achievement-obesity connection in secondary school settings and to reveal intervening social-psychological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing academic anxiety and stress will lead to better academic performance (51) , but it may also help to promote health behaviours and outcomes (52) . A recent study also emphasises that conventional physical education and other school-based physical activities alone are not sufficient to prevent the obesity epidemic (53) . Yet, further research is needed to expand this study to explore the achievement-obesity connection in secondary school settings and to reveal intervening social-psychological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…One analysis of the 2017‐2018 database, 81 for example, found that 25 states had policies that addressed the National Health Education Standards 71,72 and 15 states had policies that addressed professional development for health education. The extent to which schools comply with various component policies is not clear 85 …”
Section: Presentation Of the Theorymentioning
confidence: 99%